The rational use of opioid analgesics for cancer pain - with a critique of the WHO 3-step ladder - Ahmedzai, Sam (Henry Stewart Talks, 2009)
Who 3-step analgesic ladder for cancer pain, Overview of WHO cancer pain programme, Cancer pain: a global problem, UK national cancer patient survey, Cancer pain is still endemic in the developed world, Pain characteristics, Pain in advanced cancer, 2007 EPIC survey, What has been achieved?, The problem, The science of pain mechanisms and pain control, Cancer pain is complex, Cancer pain scenarios, Aetiology of cancer pain, Chronic pain is mediated by immune/inflammatory mechanisms, The WHO resource allocation model, Validation of WHO ladder, What has impeded progress?, What is an 'adjuvant' in pain control?, Current molecular neurotransmission targets for pain control, The solution, Several mechanism-based ways of treating cancer pain, Pyramid of modern approaches to cancer pain, Do anti-cancer treatments reduce pain?, How do opioids reduce pain and are they all the same?, Can opioids do harm?, Morphine for cancer pain, Can opioids be combined?, Has the WHO ladder altered physician attitudes to cancer pain management?, Models of pain management: dogma vs. rationality, What else can we offer besides oral morphine?, Comprehensive modern approach to analgesics for cancer pain, Towards a new mechanism-based approach